Formation of vertically oriented graphenes: what are the key drivers of growth?. (13th August 2018) - Baranov, O; Levchenko, I; Xu, S; Lim, J W M; Cvelbar, U; Bazaka, K
Abstract: Vertically oriented graphenes have been grown for more than a decade, but until now the chemical and physical mechanisms underlying their growth have not been fully defined and understood. For this reason, we build a multi-scale, multi-factor model which is thoroughly verified using a large body of experimental data to provide a significant insight into the chemical and physical processes that determine nucleation, growth and structure formation of vertically aligned graphenes in plasma environments. Roles of chemical and physical processes that cannot be directly characterized using presently available experimental techniques, e.g. surface diffusion of adatoms and radicals, are also studied using this model. The leading role of surface diffusion fluxes, rather than direct influx from the gas phase, is confirmed, with ion bombardment being a key factor in 'switching' the growth modes by generating surface defects and hence, increasing the surface adsorption energy. Thus, the hydrocarbon radicals generated on a substrate as a result of bombardment are shown to diffuse to the nanoflakes and catalyze the reactions, and serve as the primary source of material to build the nanoflakes.